Manhaj Al-Zahabi dalam Kitab Mizan Al-I'tidal - Isnayanti Isnayanti (LPPM IAIN Sultan Amai Gorontalo, 2020)
An Opus is certainly influenced by the background of science or education, the environment in which people live and the tendency of the author to produce a separate manhaj. This paper intends to discuss one of the mahjaj in the science of hadith namely al-Z|ahabi. al-Z| ahabi is one of the most well-known hadith critics in evaluating the hadith narrators. There are many works of al-Z | ahabi in the field of hadith, one of which discusses the criticism of sanad is the book of Miza> n al-I'tida> l fi> Naqd al-Rija> l, this book contains narrators who have indications da'if and matru> k so this book is often used to ensure the quality of narrators who are accused of lying, d a'if or matruk.